Quantitative Description of the Morphology and Ossification Center in the Axial Skeleton of 20-Week Gestation Formalin-Fixed Human Fetuses Using Magnetic Resonance Images - Pereda-Tapiol, J (2012)
Objectives: Human tissues are usually studied using a series of two-dimensional visualizations of in vivo or cutout specimens. However, there is no precise anatomical description of some of the processes of human fetal development. The purpose of our study is to develop a quantitative description of the normal axial skeleton by means of high-resolution three-dimensional magnetic resonance (MR) images, collected from six normal 20-week-old human fetuses fixed in formaldehyde. Methods: Fetuses were collected after spontaneous abortion and subsequently fixed with formalin. They were imaged using a 1.5T MR scanner with an isotropic spatial resolution of 200?m. The correct tissue discrimination between ossified and cartilaginous bones was confirmed by comparing the images achieved by MR scans and computerized axial tomographies. The vertebral column was segmented out from each image using a specially developed semi-automatic algorithm. Results: Vertebral body dimensions and inter-vertebral distances were larger in the lumbar region, in agreement with the beginning of the ossification process from the thoracolumbar region toward the sacral and cephalic ends. Conclusion: In this article, we demonstrate the feasibility of using MR images to study the ossification process in formalin-fixed fetal tissues. A quantitative description of the ossification centers of vertebral bodies and arches is presented. © 2012 John Wiley & Sons, Ltd.